Higenamine, a Dual Agonist for β1- and β2-Adrenergic Receptors Identified by Screening a Traditional Chinese Medicine Library - Chen, Yanmin; Guo, Bujing; Zhang, Hongda; Hu, Lihong; Wang, Jue (Planta Medica, 2019)
Chronic heart failure is the terminal stage of various cardiovascular diseases. Despite the availability of several classes of drugs, there is still an unmet need for effective treatment. Based on bench work during the past two decades, we have proposed that enhancement of β2-adrenergic receptor signaling in combination with the presently preferred β1-adrenergic receptor blockade would be a promising strategy. Chinese herbal medicines have been shown to be effective in the treatment of heart failure, although the mechanisms largely remain unknown. In the present study, we screened an herbal medicine compound/extract library for β-adrenergic receptor ligands to determine the target of certain effective botanical remedies and seek a leading compound(s) for chronic heart failure treatment. Using a high-throughput screening assay, we identified higenamine, which has a long history in chronic heart failure treatment in traditional Chinese medicine, to be a potent β-adrenergic receptor agonist. Further experiments using specific inhibitors showed that higenamine activated both β1-adrenergic receptor and β2-adrenergic receptor. Inhibition of its action by pertussis toxin (a Gi inhibitor) indicated that it is a β2-adrenergic receptor Gs/Gi dual agonist. Contractility experiments demonstrated a positive inotropic effect of higenamine. In conclusion, we found an herbal compound, higenamine, to be a dual agonist for β1/β2-adrenergic receptors with no preference in stimulating the Gs and Gi pathways in β2-adrenergic receptor signaling. Our results elucidated not only the target of higenamine to explain its pharmacological effect in treating chronic heart failure, but also the mechanisms of its cardiac toxicity.
Keywords: chronic heart failure; β-adrenergic receptor; biased signaling; agonist; higenamine